The Genetic Multiplicity- Multiple Endocrine Neoplasia type I - Anubha, Bajaj (International Journal of Infection Prevention, 2020)
Multiple endocrine neoplasia type 1 (MEN1) is a syndrome emerging from characteristic mutations of  MEN1 gene with concurrently enunciated  multiple endocrine and tumours and associated non-endocrine neoplasm. Previously designated as Werner’s syndrome, MEN1 syndrome denominates genomic mutation within  chromosome 11q13 or a  tumour suppressor  gene with a distinctive protein product nomenclated as “menin”. MEN1 syndrome demonstrates an autosomal dominant pattern of disease inheritance where genomic mutations delineate  a comprehensive (100%) disease penetrance. MEN1 gene was initially identified in 1997 upon chromosome 11q13. Although twelve genetic mutations were primarily identified, currently beyond eighteen hundred genomic mutations are scripted12. MEN1 syndrome is comprised of diverse combination of twenty or more endocrine and non-endocrine tumours exemplifying a classic triad of pituitary, parathyroid  and pancreatic  neoplasm. Diverse non endocrine tumours enunciated with MEN1 syndrome are denominated with meningioma, ependymoma or angiofibroma12. Endocrine tumours are discerned on account of excessive hormonal secretion engendered from various neoplasm or on account of neoplastic evolution. Approximately 10% instances can occur due to  a de-novo genomic variant. Offspring of an individual with MEN1 syndrome quantifies a 50% possibility of inheriting the genomic variant. Cogent prenatal diagnosis can be determined in instances where  specific genomic variant of a particular family is known. Physical, psychological and social restrictions are prevalent with MEN1 syndrome. Heterozygotes with MEN1 genetic variant are denominated as carriers and manifest a two- fold possible mortality12.
Keywords: Genetic Multiplicity; Endocrine; Neoplasia